SOCIAL DEVELOPMENT THROUGH LOCAL SPORTS COMUNITIES (AN ARTICLE) - Singh, Sandeep; Panchal, Rajesh Kumar; Jaggi, Devender Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In every society, diverse communities play a crucial role in shaping culture, behavior, and societal standards. This article focuses on the significance of sports, physical activities, and recreational pursuits. It examines how these activities contribute to the development of a well-rounded personality within the community. Engaging in sports fosters moral values and character development among the youth. Additionally, it highlights various organizations that advocate for sports and recreational activities within society. The investigator aims to explore the contributions of different communities, such as families, local groups, sports clubs, teams, and national organizations, which are vital for the youth. This is particularly relevant in light of the challenges faced by the younger generation, who may struggle to find direction and may resort to crime and negative behaviors. The research indicates that these communities play a significant role in providing youth with increased opportunities for sports participation, improved sports infrastructure, and essential resources such as facilities, equipment, and life experiences.